Multiwavelength Color Switching from Polyaniline‐Viologen Bilayer: Inching toward Versatile All‐Organic Flexible Electrochromic Device. (30th November 2022) - Ghosh, Tanushree; Kandpal, Suchita; Rani, Chanchal; Bansal, Love; Tanwar, Manushree; Kumar,, Rajesh
Abstract: Search for a versatile flexible all‐organic liquid electrolyte‐less solid–state electrochromic device continues. In this quest, a polyaniline‐Viologen‐(PANI‐EV)‐based electrochromic device has been reported and designed based on the complementary redox behavior and easy processibility. Electrochromic electrodes are first individually characterized before the device fabrication, to check their compatibility. The polyaniline electrode is electrodeposited and characterized using scanning electron microscopy and Raman techniques followed by bias dependent absorbance measurements to understand its color switching capabilities. In situ kinematics are performed on the finished solid–state device and electrochromic performance have been measured. An improved electrochromic performance can be observed as evident from <1 s switching time while switching with a color contrast of ≈75% and good cycle life. The device displays switching in visible, as well as IR and NIR regions with an application of bias as low as 1.5 V. In addition to the multiple wavelength switching, a device has also been fabricated on a plastic electrode to demonstrate all‐organic flexible liquid electrolyte less solid–state versatile electrochromic device. Abstract : Complementary redox nature of polyaniline‐viologen (PANI‐EV) enables them to be a redox pair for fabricating versatile solid–state electrochromic device. The device shows an improved electrochromic performance with less than one second switching time and good coloration efficiency. The device displays that multiwavelength switching is compatible for an all‐organic, flexible, liquid electrolyte‐less solid–state versatile electrochromic device as well.